PENGARUH MEDIA QUIZWHIZZER SEBAGAI MEDIA EVALUASI PADA MATA PELAJARAN PAI DAN BUDI PEKERTI MATERI ZAKAT KELAS IX DI SMPN 1 SUMBERREJO BOJONEGORO - Novi Damayanti; Khoirotus Silfiyah; Alaika Abdi Muhammad; Dara Nur Fadilla (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
Evaluation is a process, not a result (product). The results obtained from evaluation activities are a picture of the quality of something, both concerning value or meaning. While the activities to get to the giving of value and meaning are interesting and innovative evaluations that are very popular with students in this Alpha generation era. One of them is evaluation using Quizwhizzer media. The approach in this study uses a quantitative approach with the type of Quasi Experiment research (pseudo experiment). The quasi-experiment method (pseudo experiment) is an experimental design that has a control group, but does not function fully to control external variables that affect each sample in the control class and the experimental class totaling 30 students. The data for this study were generated from the pretest and posttest using 20 multiple choice questions. Data collection was carried out by means of observation and documentation. Data analysis techniques include validity testing, hypothesis testing to determine the significant effect on the sample. The pretest from the control group had an average value of 50.50. The posttest of the control class had an average value of 60.50. While in the experimental class the average pretest score was 50.00 and the average posttest score was 87.50. So it can be concluded that there is a significant difference between class IXH (experimental class) which was given treatment and IXC (control class) which was not given treatment. And it can also be said that H0 is rejected and H1 is accepted, meaning that there is a significant influence on the use of the quizwhizzer application as a media for evaluating PAI and Budi pekerti learning.